IMPROVING THE ENGLISH COMPETENCY OF FINAL YEAR STUDENTS THROUGH TOEFL PREPARATION TRAINING AT STIE GEMA WIDYA BANGSA - Ida Zuraida; Hendar Hendar; Heri Heryono; Atri Nadia Astarina; Dina Yulia Wijaya (LPPM Univ. Ibn Khaldun Bogor, 2026)
The fourth Sustainable Development Goal (SDG 4), Quality Education, serves as the primary foundation for this community service program (PKM). This PKM aims to enhance the English proficiency of final-year students at STIE Gema Widya Bangsa, Bandung, through TOEFL Preparation training and testing. The program was attended by 88 students from the Management, Human Resources, Marketing Management, and accounting departments. The implementation method was divided into three stages: 1) The initial stage, consisting of a pre-test to gauge fundamental abilities; 2) The core stage, involving interactive material delivery and simulations for the three TOEFL sections (Listening, Structure, and Reading); and 3) The final stage, which included a post-test and evaluation. The results showed a significant improvement in the participants' TOEFL scores. The majority of participants achieved scores in the 501-550 range, surpassing the common minimum standard. Thus, this PKM is considered effective in equipping students with relevant English language skills and enhancing their competitiveness in the job market.